First detection of porcine respirovirus 1 in Germany and the Netherlands. Issue 6 (5th May 2021) - Schuele, Leonard; Lizarazo‐Forero, Erley; Cassidy, Hayley; Strutzberg‐Minder, Katrin; Boehmer, Jan; Schuetze, Sabine; Loebert, Sandra; Lambrecht, Claudia; Harlizius, Juergen; Friedrich, Alex W.; Peter, Silke; Rossen, John W. A.; et al.
Abstract: Porcine respirovirus 1, also referred to as porcine parainfluenza virus 1 (PPIV‐1), was first detected in deceased pigs from Hong Kong in 2013. It has since then been found in the USA, Chile and most recently in Hungary. Information on the pathogenicity and global spread is sparse. However, it has been speculated to play a role in the porcine respiratory disease complex. To investigate the porcine virome, we screened 53 pig samples from 26 farms within the Dutch–German border region using shotgun metagenomics sequencing (SMg). After detecting PPIV‐1 in five farms through SMg, a real‐time reverse transcriptase PCR (RT‐qPCR) assay was designed, which not only confirmed the presence of the virus in 1 of the 5 farms but found an additional 6 positive farms. Phylogenetic analysis found the closest match to be the first detected PPIV‐1 strain in Hong Kong. The Dutch‐German region represents a significant area of pig farming within Europe and could provide important information on the characterization and circulation of porcine viruses, such as PPIV‐1. With its recent detection in Hungary, these findings suggest widespread circulation of PPIV‐1 in Central Europe, highlighting the need for further research on persistence, pathogenicity and transmission in Europe.